Korea–ASEAN Business and International Management (2006–2025): A Bibliometric Mapping - Orisoon, Kittituch; lerdwicharudii, natkrita (Korean Studies for International Management Journal, 2026)
This study examines the intellectual and thematic structure of Korea–ASEAN business and international management research published between 2006 and 2025 using a systematic bibliometric approach. The analysis draws on 163 Scopus-indexed documents and integrates performance indicators with science mapping techniques to trace publication trends, collaboration patterns, and the field’s conceptual organization. Research output increases markedly after 2016, with nearly two-thirds of the corpus published in the past decade and a peak in 2024. The field remains highly dispersed across 118 journals, reflecting its interdisciplinary character. In terms of knowledge production, South Korea is the leading contributor, followed by the United States, China, and Malaysia, alongside substantial international collaboration among major publishing countries. Thematic patterns continue to be dominated by foreign direct investment (FDI) and global value chain perspectives, with growing attention to regional integration and country-specific contexts, particularly Vietnam. Bibliographic coupling identifies four main research fronts: FDI determinants and outcomes, FDI–energy–environment linkages, knowledge transfer and organizational mechanisms, and global value chain restructuring. Co-citation analysis further indicates an intellectual base rooted in FDI–growth and spillover research, complemented by value-added trade and capability-based perspectives. The findings reveal a structural imbalance in the field. While macroeconomic approaches dominate, firm-level and organizational mechanisms remain comparatively underdeveloped despite their strong influence. This study contributes by clarifying this imbalance and outlining a research agenda focused on production-network reconfiguration, digital internationalization, sustainability governance, and multi-level designs linking firm strategy to regional policy frameworks.